Vpliv vrednotnih orientacij na telesno samopodobo in lepotne telesne prakse mladih žensk v Sloveniji, na Hrvaškem in v Srbiji - Čevnik, Lucija (visokošolska dela, 2015)
This doctoral dissertation deals with the assessment of the impact of value orientations on body image and the use of physical beauty practices by young women in Slovenia, Croatia and Serbia. After the disintegration of Yugoslavia, the countries entered an uncertain and turbulent transition period, which was dealt by them with different degrees of effectiveness. The transitional course of events as well as the historical, cultural and religious differences of each country have also left their mark on the role and position of women in each of the countries. This thesis deals with how much modernization did, in terms of modernization theory (Inglehart and Welzel, 2007), through a system of dominant value orientations the use of the media and cultural features of the countries analysed, influence the differences in the perception and understanding of the female body, which is reflected in the body image of women and the use of physical beauty practices. The theoretical part shows a historical overview of the position of women in Slovenia, Croatia and Serbia since the creation of Yugoslavia until today. This is followed by an analysis of other studies on body image, the use of beauty practices and the impact of the media on corporeality as well as the comparison of existing studies on the value orientations (of young people) in the above-mentioned countries. The empirical part analyses the impact of the factors (values, media influence, socio-demographic factors and body mass index (BMI)) on body image and recognizes their mutual influence and interconnection. The results of the analysis did not confirm a direct impact on body image values, however, the value orientationswere shown to be a relevant factor of the media impact and the use of beauty practices. Body image was also statistically significantly influenced by BMI and some socio-demographic factors (education, wealth). A significant impact of socio-demographic factors (size of place of residence, education, wealth) on values and physical practices was also proven.
Keywords: človeško telo; Disertacije; Hrvatska; indeks telesne mase; lepota; množični mediji; Samopodoba; Slovenija; Srbija; vrednote; Ženske